Can Self-Regulatory Strength Training Counter Prior Mental Exertion? A Systematic Review of Randomized Controlled Trials - Sun, He; Soh, Kim Geok; Norjali Wazir, Mohd Rozilee Wazir; Ding, Cong; Xu, Tingting; Zhang, Dong (Frontiers in Public Health, 2022)
Background: Prior mental exertion consumes self-regulation and influences any subsequent physical or cognitive performance. However, the counteractive effect of self-regulatory strength training remains unclear. Objective: This study aims to report a comprehensive systematic review investigating self-regulatory strength training programmes on physical or cognitive performance. Methods: To select relevant studies from the available literature, a thorough search was conducted on PubMed, Web of Science, EBSCOhost (CENTRAL, Psychology and Behavioural Sciences Collection, SPORTDicus), Scopus, and Google Scholar, as well as the sources of reference for grey literature. Only randomised controlled trials involving healthy humans, the strength-based self-regulation training programmes with comparable protocols, and a physical or cognitive task associated with the study were selected for review. Results: Twelve articles were included based on the selection criteria. The majority of the studies reported that self-regulatory strength training programmes can significantly counter prior mental exertion and decrement of performance, while only one study did not find such improvement. According to the strength model, a period of training increased ‘self-regulatory muscle’. Conclusion: Overall, strength as an important ingredient in the resource model of self-regulation can be trained to counter prior mental exertion and improve subsequent physical and cognitive performance. Future studies may try to apply these training programs from the field of ego depletion to the mental fatigue field.